Consultoria empresarial: o serviço social posto à prova - Azevedo, Fernanda Caldas de (2013)
Founded in a critical perspective, the purpose of this dissertation aimed to capture the business consulting of Social Work in the face of productive restructuring. Therefore, this area of professional practice was understood on the basis in the study of capitalism in its different phases and in particular of the productive restructuring (1970), which allowed the expansion of precarious work relationships, strengthening professional outsourcing process, and providing opportunities the expansion of business consultancy in the area of Social Work. Therefore, a qualitative approach was used, consisting of exploratory field research which mapped four consulting business in the state of São Paulo, which offer the practice of social work as one of their services and semi-structured interviews with social workers-business consultants. The interviews were analyzed according to the following axes: forms of commodification of the labor force, the construction process of individual and collective identities, the organization and the conditions of work, safety conditions of work and the conditions of participation in the professional class. The analytical path performed demonstrated and reaffirmed the logic for restructuring the capital and destroying of the working class, with hiddenness of social and salary losses, the priority attention to business demands and secondary care to the working class, expansion of professional experience in consulting through quarteirização (outsourced companies that outsource their services) indicating a capillarization of precarization for the professional who occupies this space and for the professional category - and among other things, there is a trend towards substitution of business professionals (formal employees) for business consultants (freelance). In summary, the issue becomes relevant for pointing out the precarization of world of work through the professional category of Social Workers; therefore this issue should be a concern of professionals, of category as a whole, and of the institutions of professional representation